2017
DOI: 10.1097/brs.0000000000002093
|View full text |Cite
|
Sign up to set email alerts
|

One-stage Surgical Management for Lumbar Brucella Spondylitis by Posterior Debridement, Autogenous Bone Graft and Instrumentation

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
2
21
0
2
Order By: Relevance
“… 126 In contrast, it has been reported that a single-stage procedure is a safe and efficient way to control infection and simultaneously reconstruct the spine. 127 , 128 Both techniques seem to be efficient; however, two-stage operations increase hospital stay and the already compromised patients may not be able to be withstand a second surgical procedure. The decision for the appropriate procedure should be based on surgical experience and general health status.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“… 126 In contrast, it has been reported that a single-stage procedure is a safe and efficient way to control infection and simultaneously reconstruct the spine. 127 , 128 Both techniques seem to be efficient; however, two-stage operations increase hospital stay and the already compromised patients may not be able to be withstand a second surgical procedure. The decision for the appropriate procedure should be based on surgical experience and general health status.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Also, only was one patient diagnosed with cervical changes in C6-C7. Similarly, other studies declared the lumbar vertebrae as the most commonly involved site in brucellosis spondylitis (40,41).…”
Section: Discussionmentioning
confidence: 79%
“…The anterior approach has the advantage in lesion identi cation and differentiation from other adjacent tissues especially in the case of abscess. It enables the direct visualization of infected lesions and therefore can clear the lesion by using less time, especially in the removal of necrotic disc tissue and destroyed vertebrae to relieve the compression from the front of the spinal canal (17). The restoration of the anterior column through intervertebral bone grafting increased the spinal stability and repaired bone defects.…”
Section: Discussionmentioning
confidence: 99%